Open access: implications for scholarly publishing and medical libraries. - Albert KM (Journal of the Medical Library Association, 2006)
Purpose: The paper reviews and analyzes the evolution of the open access (OA) publishing movement and its impact on the traditional scholarly publishing model. Procedures: A literature survey and analysis of definitions of OA, problems with the current publishing model, historical developments, funding agency responses, stakeholder viewpoints, and implications for scientific libraries and publishing are performed. Findings: The Internet's transformation of information access has fueled interest in reshaping what many see as a dysfunctional, high-cost system of scholarly publishing. For years, librarians alone advocated for change, until relatively recently when interest in OA and related initiatives spread to the scientific community, governmental groups, funding agencies, publishers, and the general public. Conclusions: Most stakeholders acknowledge that change in the publishing landscape is inevitable, but heated debate continues over what form this transformation will take. The most frequently discussed remedies for the troubled current system are the 'green' road (self-archiving articles published in non-OA journals) and the 'gold' road (publishing in OA journals). Both movements will likely intensify, with a multiplicity of models and initiatives coexisting for some time.